2015
DOI: 10.1364/boe.6.001124
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic aberration correction using region of interest based digital adaptive optics in Fourier domain OCT

Abstract: In this paper a numerical technique is presented to compensate for anisotropic optical aberrations, which are usually present across the lateral field of view in the out of focus regions, in high resolution optical coherence tomography and microscopy (OCT/OCM) setups. The recorded enface image field at different depths in the tomogram is digitally divided into smaller sub-regions or the regions of interest (ROIs), processed individually using subaperture based digital adaptive optics (DAO), and finally stitche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…For example, alternative signal collection schemes like Bessel beam illumination, dynamic focusing [71], and Gabor domain OCM [72] help maintain resolution and signal collection over large depth ranges. Computational methods like interferometric synthetic aperture microscopy [34] and CAO [35,[73][74][75] allow for the mitigation of defocus and aberrations, respectively. CAO may also enable the use of novel illumination schemes to enhance signal collection in depth [35].…”
Section: Advantages Of An Ocm-based Platform For Cell Mechanics Researchmentioning
confidence: 99%
“…For example, alternative signal collection schemes like Bessel beam illumination, dynamic focusing [71], and Gabor domain OCM [72] help maintain resolution and signal collection over large depth ranges. Computational methods like interferometric synthetic aperture microscopy [34] and CAO [35,[73][74][75] allow for the mitigation of defocus and aberrations, respectively. CAO may also enable the use of novel illumination schemes to enhance signal collection in depth [35].…”
Section: Advantages Of An Ocm-based Platform For Cell Mechanics Researchmentioning
confidence: 99%
“…ISAM is implemented at the end to correct the aberrations and defocus for all the depths simultaneously. In the cases where aberrations are significantly different from region to region, even in the same depth layer, it is possible to divide the volume into multiple regions and use different aberration correction filters for each piece, and then reassemble them to reconstruct the composite image [117]. A further simplification is the assumption of an achromatic system, where the k-dependence of the aberration correction filter .…”
Section: Cao Theorymentioning
confidence: 99%
“…Adie et al [17] showed PSF improvement after CAO processing when imaging a silicone phantom with subresolution microparticles in an astigmatic system. CAO has been successfully applied to scattering biological samples imaged by different scanning geometries, such as ex vivo rat lung tissue [17] and 3D rabbit muscle tissue [116] by point scanning FD-OCT, and grape skin [123] and ex vivo mouse adipocytes by full-field SS-OCT [117].…”
Section: Applications Of Caomentioning
confidence: 99%
“…In this way, volumetric aberration-free imaging can be achieved. This flexible processing method can be used to correct for arbitrary aberrations of high order [8, 33], and can be optimized for selected sample regions to overcome spatially varying aberrations [34]. CAO has recently been applied to in vivo imaging of the human retina for visualization of the photoreceptor mosaic [8].…”
Section: Introductionmentioning
confidence: 99%